2022
DOI: 10.12998/wjcc.v10.i9.2660
|View full text |Cite
|
Sign up to set email alerts
|

Role of metabolites derived from gut microbiota in inflammatory bowel disease

Abstract: Over the past two decades, it is improved gut microbiota plays an important role in the health and disease pathogenesis. Metabolites, small molecules produced as intermediate or end products of microbial metabolism, is considered as one of the major interaction way for gut microbiota with the host. Bacterial metabolisms of dietary substrates, modification of host molecules or bacteria are the major source of metabolites. Signals from microbial metabolites affect immune maturation and homeostasis, host energy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 167 publications
(164 reference statements)
1
24
0
1
Order By: Relevance
“…50 mg samples showed a significantly higher mean number of m/z features and mean number of identified metabolites in comparison to 20 mg samples. Furthermore, the mean signal intensity given by 50 mg samples (2.5x10 7 ) was significantly increased compared to 20 mg samples (1.1x10 7 ). Levels of altered metabolites were calculated from the differential analysis of sample weight and expressed as the percentage of significantly increased metabolites between groups.…”
Section: Analysis Of Sample Weightmentioning
confidence: 80%
See 1 more Smart Citation
“…50 mg samples showed a significantly higher mean number of m/z features and mean number of identified metabolites in comparison to 20 mg samples. Furthermore, the mean signal intensity given by 50 mg samples (2.5x10 7 ) was significantly increased compared to 20 mg samples (1.1x10 7 ). Levels of altered metabolites were calculated from the differential analysis of sample weight and expressed as the percentage of significantly increased metabolites between groups.…”
Section: Analysis Of Sample Weightmentioning
confidence: 80%
“…The accurate quantification of metabolites in faecal samples therefore holds value in a wide range of research areas. A clear role of faecal metabolomics has been demonstrated in the field of gastrointestinal disease, including inflammatory bowel disease (IBD) [7] and coeliac disease (CoD) [8]. Although the aetiology of such diseases remains elusive, shifts in metabolic profile are associated with disease activity and may represent central components of pathogenesis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has become increasingly clear that T cell activation, differentiation, and effector functions are closely associated with cellular metabolic programs, including glycolysis, FA synthesis, and mitochondrial metabolism ( Bantug et al., 2018 ). There is compelling evidence that the etiology of IBDs may be associated with various metabolic dysregulations ( Alexander et al., 2022 ; Zheng et al., 2022 ). It has been demonstrated that parasite-derived products have a strong ability to regulate metabolism in the host body ( Zhu et al., 2014 ; Cai et al., 2021 ; Fisher et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, through the construction of the “drug - component - target - disease” network, the 8 active ingredients with higher degree values were analyzed to provide a reference for identifying the compatibility relationship between zedoary turmeric and trisomes and were found to jointly participate in the regulation of IBD intestinal fibrosis[ 18 ]. Studies have proven that ivy saponin has anti-inflammatory, anticoagulant, antidepression, antitumor, antibacterial and other effects[ 19 ]. β-Sitosterol exerts antioxidant, cholesterol-lowering, anti-inflammatory, immunomodulatory and antitumor effects and can also enhance the secretion of IL-2 and interferon-Îł, inhibit the secretion of IL-4, and exert anti-inflammatory effects by inhibiting IL-6 and tumor necrosis factor[ 20 ].…”
Section: Discussionmentioning
confidence: 99%